1980
DOI: 10.1152/ajpendo.1980.238.1.e69
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive determination of local cerebral metabolic rate of glucose in man

Abstract: A method for the determination of local cerebral metabolic rates of glucose (LCMRGlc) in normal man is described. The method employs [18F]2-fluoro-2-deoxy-D-glucose (FDG) and emission-computed tomography (ECT). FDG was injected intravenously as a bolus. Radioactivities in separate brain regions were measured with ECT. Plasma FDG concentration following injection was measured from blood samples. A mathematical model that describes the kinetics of FDG transports was employed to determine the transport rate const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
434
4
2

Year Published

1983
1983
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(453 citation statements)
references
References 19 publications
13
434
4
2
Order By: Relevance
“…This large difference is surprising, but, on the other hand, an earlier value of 15.3 (re calculated with LC = 0.52) reported for the same scanner (Huang et al, 1980) but using 2 to 3-cm2 regions of interest, is more comparable, being only 11% greater than the present values. We suspect that the use of anatomical atlases by Mazziotta et al to determine regions of interest may have led to a large partial volume error in the white matter measurements.…”
Section: Comparison With Previous Petcontrasting
confidence: 85%
“…This large difference is surprising, but, on the other hand, an earlier value of 15.3 (re calculated with LC = 0.52) reported for the same scanner (Huang et al, 1980) but using 2 to 3-cm2 regions of interest, is more comparable, being only 11% greater than the present values. We suspect that the use of anatomical atlases by Mazziotta et al to determine regions of interest may have led to a large partial volume error in the white matter measurements.…”
Section: Comparison With Previous Petcontrasting
confidence: 85%
“…
Summary: Measurement of the local cerebral metabolic rate of glucose (LCMRGlc) with the fluorodeoxyglucose (FDG) method requires the utilization of appropriate val ues for the rate constants of the transport and phosphor ylation processes, We measured these rate constants as a function of age to determine whether a decline in LCMRGlc as a function of age, in prior studies with the The deoxyglucose method originally developed by Sokoloff et aL (1977) and applied to humans by Reivich et aL (1979), Phelps et aL (1979), andHuang et aL (1980) provides a measurement of the local cerebral metabolic rate of glucose (LCMRGlc). The Sokoloff model, as modified by Phelps et aL (1979) and Huang et aL (1980), requires the rate constants kl* and k2* for forward and reverse membrane transport of fluorodeoxyglucose (FDG), and k3* and k4* for phosphorylation of FDG and dephosphory lation of FDG-6-P04' Prior investigations have demonstrated that in altered states of metabolism, values obtained for LCMRGlc can be in error if inappropriate rate constants are used (Hawkins et aI., 1981; Huang et aI., 1981 may occur, although the most significant errors occur in hypo metabolic states.

Several investigators have demonstrated a de cline in the rate of human cerebral glucose metabo lism (CMRGlc) as a function of age, using inert gas clearance methods for measuring flow and cal culating glucose metabolism as the product of cere bral blood flow (CBF) and cerebral A-V glucose difference (Dastur et aI., 1963; Gottstein et aI., 1971;Gottstein and Held, 1979).

…”
mentioning
confidence: 99%
“…K 1 is the transport rate from plasma to brain tissue with units ml/100g/minute, k 2 is the transport rate back from brain to blood vessel with units 1/minute, k 3 is the phosphorylation rate of intra-cellular FDG by hexokinase enzymes to FDG-6-phosphate with units 1/minute. Because the scanning interval 60 minutes is relatively small, it will be difficult to accurately estimate the dephosphorylation rate of intra-cellular FDG-6-phosphate back to FDG, k 4 , [17]. We thus set k 4 , which is itself small, to zero.…”
Section: An Algorithm For Recovering the Input Functionmentioning
confidence: 99%
“…The bounds used are based on experimental results [17] for both gray and white matter from 13 but with doubling of upper bounds and halving of lower bounds such that the feasible space is not too conservatively estimated. Time delay between the TTACs and the input function is removed by automatically shifting the TTACs such that the first peak of each is aligned with v τp .…”
Section: An Algorithm For Recovering the Input Functionmentioning
confidence: 99%
See 1 more Smart Citation